Psycological Factors Influencing Pro-Environmental Behavior in Urban Areas - Geofakta Razali; Yusuf Iskandar; Sri Fatmawati; Rahmat Hidayat; Muhammad Umer Farooq Mujahid (Westscience Press, 2023)
This research investigates the psychological factors influencing pro-environmental behavior among adolescents in Bandung City, Indonesia. Adopting a quantitative approach, a cross-sectional survey was conducted to collect data from a representative sample of 500 adolescents aged 14 to 18. The study focused on assessing environmental attitudes, environmental knowledge, environmental consciousness, and environmental self-efficacy about pro-environmental behavior. Additionally, the potential moderating effects of socio-demographic factors on the relationship between psychological factors and pro-environmental behavior were explored. The findings reveal that environmental attitudes and self-efficacy are the strongest predictors of pro-environmental behavior. Ecological consciousness and environmental knowledge also play significant roles in influencing sustainable actions. Furthermore, education level was found to moderate the relationship between environmental learning and pro-environmental behavior. The implications of these findings are discussed, providing recommendations for targeted interventions to promote sustainable behavior among adolescents in urban areas.